Antiplatelet Therapy with Cangrelor in Patients Undergoing Surgery after Coronary Stent Implantation: A Real-World Bridging Protocol Experience - Rossini, Roberta; Masiero, Giulia; Fruttero, Claudia; Passamonti, Enrico; Calvaruso, Elba; Cecconi, Moreno; Carlucci, Cesare; Mojoli, Marco; Guido, Parodi; Talanas, Giuseppe; Pierini, Simona; Canova, Paolo; De Cesare, Nicoletta; Luceri, Stefania; Barzaghi, Nicoletta; Melloni, Giulio; Baralis, Giorgio; Locatelli, Alessandro; Musumeci, Giuseppe; Angiolillo, Dominick J. (TH Open, 2020)
Objective The aim of the study is to describe the real-world use of the P2Y12 inhibitor cangrelor as a bridging strategy in patients at high thrombotic risk after percutaneous coronary intervention (PCI) and referred to surgery requiring perioperative withdrawal of dual antiplatelet therapy (DAPT).Materials and Methods We collected data from nine Italian centers on patients with previous PCI who were still on DAPT and undergoing nondeferrable surgery requiring DAPT discontinuation. A perioperative standardized bridging protocol with cangrelor was used.Results Between December 2017 and April 2019, 24 patients (mean age 72 years; male 79%) were enrolled. All patients were at high thrombotic risk after PCI and required nondeferrable intermediate to high bleeding risk surgery requiring DAPT discontinuation (4.6 ± 1.7 days). Cangrelor infusion was started at a bridging dose (0.75 µg/kg/min) 3 days before planned surgery and was discontinued 6.6 ± 1.5 hours prior to surgical incision. In 55% of patients, cangrelor was resumed at 9 ± 6 hours following surgery for a mean of 39 ± 38 hours. One cardiac death was reported after 3 hours of cangrelor discontinuation prior to surgery. No ischemic outcomes occurred after surgery and up to 30-days follow-up. The mean hemoglobin drop was <2 g/dL; nine patients received blood transfusions consistent with the type of surgery, but no life-threatening or fatal bleeding occurred.Conclusion Perioperative bridging therapy with cangrelor is a feasible approach for stented patients at high thrombotic risk and referred to surgery requiring DAPT discontinuation. Larger studies are warranted to support the safety of this strategy.
Keywords: antiplatelet therapy; stent; surgery; bridging; cangrelor